Physical culture as the most important factor in the formation of a comprehensively developed personality - Kiryanova L.A.; Markov D.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study. Exercise and regular sports activities are critically important for the health and well-being of people of all ages. This question is especially important for schoolchildren and university students whose studies involve intense mental and emotional work. However, statistics show that a significant proportion of school and university students do not devote enough time to physical activity, preferring other activities in their free time. It is important that physical education promotes the development of students’ teamwork and communication skills. The purpose of this study is to examine the importance of physical culture in shaping the personality and healthy lifestyle of students. Methods and structure of the study. The experiment involved students of the 5th "B" class of secondary school No. 6 in St. Petersburg. The study revealed that many students consider regular physical education and sports activities only as part of the curriculum. In this case, some students perceive physical activity as a process where the main thing is the result, namely the mark, rather than maintaining their health and developing self–discipline. Results and conclusions. After the experiment, students became more willing to attend physical education classes and take the initiative in organizing sports games; many girls and boys showed interest in team sports, which led to an increase in the number of students attending sports sections both at school and outside; children began to feel more confident, became more open and it’s easier to establish contacts with peers; many have realized and understood the importance of a healthy diet.